Ultra-diluted Arsenic Trioxide Induced Cytokine Changes in HepG2 Cell Line - Singh, Bahnishikha; Chatterjee, Debasmita; Bandyopadhyay, Sanket; Das, Satadal (Asian Journal of Biological and Life Sciences)
As an alternative medicine ultra-diluted arsenic is used for problems in the digestive tract, upset stomach, sleep disorders, allergies, psoriasis, syphilis, asthma, disorders in the muscles, joints and bones, haemorrhoids, cough, pruritus, cancer, and pain. In this study, we are interested in observing cytokine expression changes which may help some understanding of the proper use of such medicine. Due to a similarity in the expression of alterations in the chemical activity of drug or integral transmembrane proteins in the cells on various metabolic pathways, the use of HepG2 cells as an experimental model cell line for such study of hepatocytes is well known. Cytopathic Effects (CPE), MTT assay, DNA fragmentation, apoptotic gene expressions, and cytokine gene expressions caused by ultra-diluted arsenic on HepG2 cells were studied. The cytokine environment of the challenged HepG2 cells was delineated by a quantitative Real-Time Polymerase Chain Reaction (qRT-PCR) study to observe gene expression changes compared to control gene β-actin. All findings indicated a strong apoptotic gene expression change caused by this medicine on HepG2 cells. There were rounding of the cells in CPE, non-viable findings in methylene blue staining, cytotoxic nature in MTT assay, and DNA-fragmentations indicated gross cellular damage. There was an up-regulation of pro-inflammatory cytokines and a down-regulation of anti-inflammatory cytokines with increased gene expression of interferon-gamma. In conclusion, ultra-diluted arsenic can potentially alter the expression of apoptotic genes and different cytokine genes and also induce an apoptotic pathway in the HepG2 cells
Keywords: CPE; Cytokines.; HepG2 cell line; MTT assay; Ultra-diluted arsenic